UPAYA GREENPEACE DALAM MENDUKUNG FORUM RAKYAT BALI TOLAK REKLAMASI TELUK BENOA (FORBALI) TAHUN 2012-2018 - Laksmi Pebriyanti, Ni Nengah Susi; Sushanti, Sukma; Priadarsini, Ni Wayan Rainy (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2022)
This research aims to describe about the planning of Benoa Bay reclamation in Bali that has been opposed by Forum Rakyat Bali Tolak Reklamasi Teluk Benoa (ForBALI). The planning of Benoa Bay reclamation is determined to get negative impacts for environment and social activity of Balinese people. This research also explains Greenpeace efforts to support ForBALI reject the planning of Benoa Bay reclamation. Those efforts shown in Greenpeace actions together with ForBALI. The data in this research was analyzed using qualitative descriptive method with secondary data source by Social Movement concept and Environmental Non-Governmental Organization concept. This research perceives that Greenpeace’s effort to support ForBALI as a Social Movement rejects the planning of Benoa Bay reclamation with the purpose to avoid negative impacts of reclamation, especially the impacts to nature and environment by using the functions of Environmental Non-Governmental Organization. Keywords: Benoa Bay reclamation, Environmental Non-Governmental Organization, ForBALI, Greenpeace, Social Movement